Bifunctional Au@Bi2Se3 Core–Shell Nanoparticle for Synergetic Therapy by SERS‐Traceable AntagomiR Delivery and Photothermal Treatment. Issue 38 (23rd August 2018) - Mohammadniaei, Mohsen; Lee, Taek; Bharate, Bapurao G.; Yoon, Jinho; Choi, Hye Kyu; Park, Soo‐jeong; Kim, Junghoon; Kim, Jungho; Choi, Jeong‐Woo
Abstract: For the first time, topological insulator bismuth selenide nanoparticles (Bi2 Se3 NP) are core–shelled with gold (Au@Bi2 Se3 ) i) to represent considerably small‐sized (11 nm) plasmonic nanoparticles, enabling accurate bioimaging in the near‐infrared region; ii) to substantially improve Bi2 Se3 biocompatibility, iii) water dispersibility, and iv) surface functionalization capability through straightforward gold–thiol interaction. The Au@Bi2 Se3 is subsequently functionalized for v) effective targeting of SH‐SY5Y cancer cells, vi) disrupting the endosome/lysosome membrane, vii) traceable delivery of antagomiR‐152 and further synergetic oncomiR knockdown and photothermal therapy (PTT). Unprecedentedly, it is observed that the Au shell thickness has a significant impact on evoking the exotic plasmonic features of Bi2 Se3 . The Au@Bi2 Se3 possesses a high photothermal conversion efficiency (35.5%) and a remarkable surface plasmonic effect (both properties are approximately twofold higher than those of 50 nm Au nanoparticles). In contrast to the siRNA/miRNA delivery methods, the antagomiR delivery is based on strand displacement, in which the antagomiR‐152 is displaced by oncomiR‐152 followed by a surface‐enhanced Raman spectroscopy signal drop. This enables both cancer cell diagnosis and in vitro real‐time monitoring of the antagomiR release. This selective PTT nanoparticle can also efficiently target solid tumors and undergo in vivo PTT, indicating its potential clinical applications. Abstract : For the first time, the topological insulator (TI), bismuth selenide nanoparticle (Bi2 Se3 NP) is core–shelled with Au (Au@Bi2 Se3, 11 nm), representing considerable plasmonic features, biocompatibility and surface functionalization capability. Functionalization of Au@Bi2 Se3 enabled efficient theranostics of neuroblastoma cells through the expression level determination and traceable delivery of antagomiR‐152 following by an efficient synergetic oncomiR inhibition and photothermal therapy in‐vivo.